Biological characters of Euplectrus xanthocephalus Girault (Hym.: Eulophidae) ectoparasite on Spodoptera litura Fabr. larvae - Thu, Nguyen Thi; Lan, Tran Ngoc; Con, Vu Quang (Academia Journal of Biology, 2012)
Research on biological characters of Euplectrus xanthocephalus ectoparasite on Spodoptera litura Fabr. larvae in Nghe An province shows the following results: In rearing condition at 25oC, 67% RH, life cycle of Euplectrus xanthocephalus is 14,95 ± 0,09 days; E. xanthocephalus is ectoparasite on Spodoptera litura Fabr. larvae from 1 instar to 4 instar larvae, specially the highest parasitic rate concentrate on 2 instar and 3 instar larvae of the host. They do not parasite on other age of Spodoptera litura Fabr. larvae (5 instar and 6 instar larvae); Eggs were laid on all three thoracic segments and abdominal segments 1-8, with a maximum number of eggs laid on the third thoracic segment to the second abdominal segments; Most of E. xanthocephalus eggs were laid on back of host, some of them on side and the eggs were not laid on venter of host; Sex ratio (female: male) is 2: 1. Key words: Biological characters, ectoparasite, life cycle, suitable instars for parasitizing, Euplectrus xanthocephalus, Spodoptera litura.